2023
DOI: 10.1017/s0031182023000343
|View full text |Cite
|
Sign up to set email alerts
|

Control of gastrointestinal helminths in small ruminants to prevent anthelmintic resistance: the Italian experience

Abstract: Helminth infections are ubiquitous in grazing ruminants and cause significant costs due to production losses. Moreover, anthelmintic resistance (AR) in parasites is now widespread throughout Europe and poses a major threat to the sustainability of modern ruminant livestock farming. Epidemiological data on the prevalence and distribution of gastrointestinal nematodes, cestodes and liver-and rumen-flukes in Italian small ruminants are outdated and fragmentary. However, anthelmintics are commonly used to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 84 publications
(119 reference statements)
0
15
0
Order By: Relevance
“…Top of Form Use of the multiple control strategies can reduce the risk of evolution of pathogen. Strategies to prevent anthelmintic resistance are described previously by other colleagues in Italy (Maurizio et al, 2023;Zanzani et al, 2014). Also the use of herbal anthelmintics can be an alternative that is cheap, safe and can overcome the problem of resistance with the presence of multitarget compounds (Liu et al, 2020;Mares et al, 2023;Barua et a l., 2023).…”
Section: Resultsmentioning
confidence: 94%
“…Top of Form Use of the multiple control strategies can reduce the risk of evolution of pathogen. Strategies to prevent anthelmintic resistance are described previously by other colleagues in Italy (Maurizio et al, 2023;Zanzani et al, 2014). Also the use of herbal anthelmintics can be an alternative that is cheap, safe and can overcome the problem of resistance with the presence of multitarget compounds (Liu et al, 2020;Mares et al, 2023;Barua et a l., 2023).…”
Section: Resultsmentioning
confidence: 94%
“…The usefulness of comparing and discussing control practices has already been demonstrated at the European level through different collaborative projects (Charlier et al ., 2022 ), however this exercise is still lacking at the national level. The Italian perspective on the control of gastrointestinal helminth infections was deeply analysed during the symposium and subsequently reported in this SI (Maurizio et al ., 2023 ). The work includes a nationwide epidemiological update on parasite prevalence and on the possible emergence of anthelmintic resistance.…”
Section: Selected Outcomes From the Symposiamentioning
confidence: 99%
“…The findings showed that, in sheep and goats, the average farm-level prevalence of AR was 48 and 51% for benzimidazoles, 29 and 44% for macrocyclic lactones other than moxidectin, and 32 and 20% for levamisole ( 16 , 17 ). There have not been many published cases of AR in small ruminants in Italy against levamisole, macrocyclic lactones, and benzimidazoles ( 18 ). Nevertheless, in 2007, there were reports of AR in small ruminants in central and southern Italy for benzimidazoles, levamisole, and ivermectin ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%